EFFECTS OF SEASONALITY, FORCED BY ORBITAL-INSOLATION CYCLES, ON OFFSHORE MOLLUSCAN FAUNAL CHANGE DURING RAPID WARMING IN THE SEA OF JAPAN - Kitamura A. (My University, 2004)
During oxygen isotope stages 50 to 26, an offshore environment that was unsuitable for both cold- and warm-water molluscs may have temporarily prevailed in the southern Sea of Japan. This inner- to outer-shelf environment existed with a lateral scale of a few kilometers and a vertical scale of a few tens of meters during at least three transitions from oxygen isotope stages 48 to 47, 44 to 43 and 32 to 31. These deglaciation periods coincided with the three highest peaks of July solar insolation at 65°N (495, 493 and 500 W/m2) between oxygen isotope stages 50 and 26. This implies that anomalously high seasonality induced by orbital-insolation cycles is likely to have played an important role in establishing non-analog benthic communities with a very low density and diversity of molluscs in the early Pleistocene Sea of Japan.
Keywords: EARLY PLEISTOCENE; MARINE MOLLUSCAN COMMUNITIES; MILANKOVITCH CYCLES; SEA OF JAPAN; Pleistocene; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен